Yap/Taz activity is associated with increased expression of phosphoglycerate dehydrogenase that supports myoblast proliferation - Marius Meinhold; Sander Verbrugge; Andi Shi; Martin Schönfelder; Lore Becker; Richard T. Jaspers; Peter S. Zammit; Henning Wackerhage (Cell and Tissue Research, 2024)
In skeletal muscle, the Hippo effector Yap promotes satellite cell, myoblast, and rhabdomyoblast proliferation but prevents myogenic differentiation into multinucleated muscle fibres. We previously noted that Yap drives expression of the first enzyme of the serine biosynthesis pathway, phosphoglycerate dehydrogenase ( Phgdh ). Here, we examined the regulation and function of Phgdh in satellite cells and myoblasts and found that Phgdh protein increased during satellite cell activation. Analysis of published data reveal that Phgdh mRNA in mouse tibialis anterior muscle was highly expressed at day 3 of regeneration after cardiotoxin injection, when markers of proliferation are also robustly expressed and in the first week of synergist-ablated muscle. Finally, siRNA-mediated knockdown of PHGDH significantly reduced myoblast numbers and the proliferation rate. Collectively, our data suggest that Phgdh is a proliferation-enhancing metabolic enzyme that is induced when quiescent satellite cells become activated.

Knockout mouse models as a resource for the study of rare diseases - Patricia da Silva-Buttkus; Nadine Spielmann; Tanja Klein-Rodewald; Christine Schütt; Antonio Aguilar-Pimentel; Oana V. Amarie; Lore Becker; Julia Calzada-Wack; Lillian Garrett; Raffaele Gerlini; Markus Kraiger; Stefanie Leuchtenberger; et al. (Mammalian Genome, 2023)
Rare diseases (RDs) are a challenge for medicine due to their heterogeneous clinical manifestations and low prevalence. There is a lack of specific treatments and only a few hundred of the approximately 7,000 RDs have an approved regime. Rapid technological development in genome sequencing enables the mass identification of potential candidates that in their mutated form could trigger diseases but are often not confirmed to be causal. Knockout (KO) mouse models are essential to understand the causality of genes by allowing highly standardized research into the pathogenesis of diseases. The German Mouse Clinic (GMC) is one of the pioneers in mouse research and successfully uses (preclinical) data obtained from single-gene KO mutants for research into monogenic RDs. As part of the International Mouse Phenotyping Consortium (IMPC) and INFRAFRONTIER, the pan-European consortium for modeling human diseases, the GMC expands these preclinical data toward global collaborative approaches with researchers, clinicians, and patient groups. Here, we highlight proprietary genes that when deleted mimic clinical phenotypes associated with known RD targets ( Nacc1, Bach2, Klotho alpha ). We focus on recognized RD genes with no pre-existing KO mouse models ( Kansl1l, Acsf3, Pcdhgb2, Rabgap1, Cox7a2 ) which highlight novel phenotypes capable of optimizing clinical diagnosis. In addition, we present genes with intriguing phenotypic data ( Zdhhc5, Wsb2 ) that are not presently associated with known human RDs. This report provides comprehensive evidence for genes that when deleted cause differences in the KO mouse across multiple organs, providing a huge translational potential for further understanding monogenic RDs and their clinical spectrum. Genetic KO studies in mice are valuable to further explore the underlying physiological mechanisms and their overall therapeutic potential.

Skeletal muscle phenotyping of Hippo gene-mutated mice reveals that Lats1 deletion increases the percentage of type I muscle fibers - Fakhreddin Yaghoob Nezhad; Annett Riermeier; Martin Schönfelder; Lore Becker; Martin Hrabĕ de Angelis; Henning Wackerhage (Transgenic Research, 2022)
The Hippo signal transduction network regulates transcription through Yap/Taz-Tead1-4 in many tissues including skeletal muscle. Whilst transgenic mice have been generated for many Hippo genes, the resultant skeletal muscle phenotypes were not always characterized. Here, we aimed to phenotype the hindlimb muscles of Hippo gene-mutated Lats1 −/− , Mst2 −/− , Vgll3 −/− , and Vgll4 +/− mice. This analysis revealed that Lats1 −/− mice have 11% more slow type I fibers than age and sex-matched wild-type controls. Moreover, the mRNA expression of slow Myh7 increased by 50%, and the concentration of type I myosin heavy chain is 80% higher in Lats1 −/− mice than in age and sex-matched wild-type controls. Second, to find out whether exercise-related stimuli affect Lats1, we stimulated C2C12 myotubes with the hypertrophy agent clenbuterol or the energy stress agent AICAR. We found that both stimulated Lats1 expression by 1.2 and 1.3 fold respectively. Third, we re-analyzed published datasets and found that Lats1 mRNA in muscle is 63% higher in muscular dystrophy, increases by 17–77% after cardiotoxin-induced muscle injury, by 41–71% in muscles during overload-induced hypertrophy, and by 19–21% after endurance exercise when compared to respective controls. To conclude, Lats1 contributes to the regulation of muscle fiber type proportions, and its expression is regulated by physiological and pathological situations in skeletal muscle.

A comprehensive phenotypic characterization of a whole-body Wdr45 knock-out mouse - Caroline A. Biagosch; Silvia Vidali; Michael Faerberboeck; Svenja-Viola Hensler; Lore Becker; Oana V. Amarie; Antonio Aguilar-Pimentel; Lillian Garrett; Tanja Klein-Rodewald; Birgit Rathkolb; Enrica Zanuttigh; Julia Calzada-Wack; et al. (Mammalian Genome, 2021)
Pathogenic variants in the WDR45 (OMIM: 300,526) gene on chromosome Xp11 are the genetic cause of a rare neurological disorder characterized by increased iron deposition in the basal ganglia. As WDR45 encodes a beta-propeller scaffold protein with a putative role in autophagy, the disease has been named Beta-Propeller Protein-Associated Neurodegeneration (BPAN). BPAN represents one of the four most common forms of Neurodegeneration with Brain Iron Accumulation (NBIA). In the current study, we generated and characterized a whole-body Wdr45 knock-out (KO) mouse model. The model, developed using TALENs, presents a 20-bp deletion in exon 2 of Wdr45 . Homozygous females and hemizygous males are viable, proving that systemic depletion of Wdr45 does not impair viability and male fertility in mice. The in-depth phenotypic characterization of the mouse model revealed neuropathology signs at four months of age, neurodegeneration progressing with ageing, hearing and visual impairment, specific haematological alterations, but no brain iron accumulation. Biochemically, Wdr45 KO mice presented with decreased complex I (CI) activity in the brain, suggesting that mitochondrial dysfunction accompanies Wdr45 deficiency. Overall, the systemic Wdr45 KO described here complements the two mouse models previously reported in the literature (PMIDs: 26,000,824, 31,204,559) and represents an additional robust model to investigate the pathophysiology of BPAN and to test therapeutic strategies for the disease.

A comprehensive and comparative phenotypic analysis of the collaborative founder strains identifies new and known phenotypes - Heike Kollmus; Helmut Fuchs; Christoph Lengger; Hamed Haselimashhadi; Molly A. Bogue; Manuela A. Östereicher; Marion Horsch; Thure Adler; Juan Antonio Aguilar-Pimentel; Oana Veronica Amarie; Lore Becker; Johannes Beckers; et al. (Mammalian Genome, 2020)
The collaborative cross (CC) is a large panel of mouse-inbred lines derived from eight founder strains (NOD/ShiLtJ, NZO/HILtJ, A/J, C57BL/6J, 129S1/SvImJ, CAST/EiJ, PWK/PhJ, and WSB/EiJ). Here, we performed a comprehensive and comparative phenotyping screening to identify phenotypic differences and similarities between the eight founder strains. In total, more than 300 parameters including allergy, behavior, cardiovascular, clinical blood chemistry, dysmorphology, bone and cartilage, energy metabolism, eye and vision, immunology, lung function, neurology, nociception, and pathology were analyzed; in most traits from sixteen females and sixteen males. We identified over 270 parameters that were significantly different between strains. This study highlights the value of the founder and CC strains for phenotype-genotype associations of many genetic traits that are highly relevant to human diseases. All data described here are publicly available from the mouse phenome database for analyses and downloads.

Fgf9 Y162C Mutation Alters Information Processing and Social Memory in Mice - Lillian Garrett; Lore Becker; Jan Rozman; Oliver Puk; Tobias Stoeger; Ali Önder Yildirim; Alexander Bohla; Oliver Eickelberg; Wolfgang Hans; Cornelia Prehn; Jerzy Adamski; Thomas Klopstock; et al. (Molecular Neurobiology, 2018)

Serum Response Factor (SRF) Ablation Interferes with Acute Stress-Associated Immediate and Long-Term Coping Mechanisms - Annemarie Zimprich; Gabi Mroz; Christopher Meyer zu Reckendorf; Sofia Anastasiadou; Philip Förstner; Lillian Garrett; Sabine M. Hölter; Lore Becker; Jan Rozman; Cornelia Prehn; Birgit Rathkolb; Kristin Moreth; et al. (Molecular Neurobiology, 2017)

Viable Ednra Y129F mice feature human mandibulofacial dysostosis with alopecia (MFDA) syndrome due to the homologue mutation - Sibylle Sabrautzki; Michael A. Sandholzer; Bettina Lorenz-Depiereux; Robert Brommage; Gerhard Przemeck; Ingrid L. Vargas Panesso; Alexandra Vernaleken; Lillian Garrett; Katharina Baron; Ali O. Yildirim; Jan Rozman; Birgit Rathkolb; et al. (Mammalian Genome, 2016)

Innovations in phenotyping of mouse models in the German Mouse Clinic - Helmut Fuchs; Valérie Gailus-Durner; Susanne Neschen; Thure Adler; Luciana Caminha Afonso; Juan Antonio Aguilar-Pimentel; Lore Becker; Alexander Bohla; Julia Calzada-Wack; Christian Cohrs; Anna Dewert; Barbara Fridrich; et al. (Mammalian Genome, 2012)

Microphthalmia, parkinsonism, and enhanced nociception in Pitx3 416insG mice - Michael Rosemann; Alesia Ivashkevich; Jack Favor; Claudia Dalke; Sabine M. Hölter; Lore Becker; Ildikó Rácz; Ines Bolle; Martina Klempt; Birgit Rathkolb; Svetoslav Kalaydjiev; Thure Adler; et al. (Mammalian Genome, 2010)